Perkembangan Wilayah Cirebon Timur Masa Kolonial Hindia Belanda - Mustaqim Asteja (PANALUNGTIK, 2024)
Eastern Cirebon is a strategic border region that underwent fundamental transformation under the administration of the Dutch East Indies Colonial Government (1681–1942), yet its development has not been extensively examined in a comprehensive manner. This research analyzes the development of the Eastern Cirebon region, focusing on the political-administrative transformation following the early 20th-century decentralization and the role of the sugar industry in shaping the colonial economy. Employing a historical research method with a historical archaeology approach, data were collected from colonial archives (Regerings-Almanak, staatsblad, maps) and local manuscripts, then verified, analyzed thematically, and structured into historical narrative. The findings indicate that Eastern Cirebon underwent intensive bureaucratization, evolving from a sultanate territory into a district within the regency structure. The 1903 decentralization policy triggered repeated territorial reorganization. The sugar industry emerged as the primary economic driver, creating patterns of dependency and exploitation of local labor. The discussion reveals complex interactions between colonial policy, extractive economics, and local social structures. The development of Eastern Cirebon resulted from dynamic interactions among the continuously evolving colonial administrative system, the extractive sugar plantation economy, and the socio-cultural context of the local community. This transformation shaped the region’s bureaucratic and economic landscape, leaving a structural legacy that persisted beyond independence.